The Use of Story Mapping in Teaching and Learning Narrative Text Writing - Riffani, Abdullah Farhan (RETAIN : Journal of Research in English Language Teaching, 2022)
Writing narrative text is one of the skills that must be mastered by every junior high school student. However,in reality,there are still manystudents who have difficultywriting narrative text independently. Several learning methodscan be used by the teacher to teach narrative text effectively in the classroom, one of which is by using a story map. This researchaimsto know how teachers implement story mapsin narrative text learning and to determine students' perceptions of story map media in narrative text learning. The research was conducted ina qualitative research design. Data collection techniques used in this study were observation and questionnaires. The research subjects in this study were 20 students inthe ninth-graderMTSN Darul Ulum in Sidoarjo and their English teacher. The results showed that the learning carried out by the teacher in implementing the story map media was not optimal because there were procedural steps that were skipped. However, students' perceptions of the use of story map media in narrative text learning in the classroom are quite good. Most students stated that they could understand narrative texts more deeply through the use of story maps as media. They also said that the media was interesting and made the learning process fun. However, some studentsgave different responses. They said that they faced difficulties in using story map media. They argue that the use of this media requires quite a lot of time and space to make the learning process less than optimal